The Role Of Family In Creating A Religious Atmosphere At Schools - Husnulloh, Alfiah Ilmi (EduGrows: Education and Learning Review, 2025)
Instilling religious values ​​in schools cannot be separated from the role of the family, because the family is the first place for children to learn. This study aims to see how the role of the family helps shape a religious atmosphere in schools. This can be done through good habits that are usually carried out at home or parental participation in religious activities at school. This study uses a library research method or library study with a qualitative approach. The results of the study show that the family plays a very important role in maintaining the continuity of religious values ​​between home and school. Parental support such as providing good examples, supervising children, and establishing good communication with the school has been shown to strengthen the religious atmosphere in schools. This study suggests that cooperation between families and schools be improved to create a comprehensive and religious educational environment.